Dialogic feedback in English Language Teaching (ELT): Modalities, outcomes, and research trends - Susanti, Ani; Sharif, Tengku Intan Suzila Tengku; Masardo, Alex (English Language Teaching Educational Journal, 2025)
This systematic literature review examines dialogic feedback research in English Language Teaching (ELT) based on 23 empirical studies published between 2010 and 2025. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, the review applied a rigorous selection and screening process to ensure transparency and replicability. Six main modalities of dialogic feedback are identified: face-to-face dialogic feedback, written dialogic feedback, technology-mediated dialogic feedback, peer dialogic feedback, supervisory dialogic feedback, and teacher professional development dialogic feedback This typology reflects variations in feedback interaction modes, participants, and instructional settings, offering a more nuanced framework for understanding how dialogic feedback operates across formal and informal learning contexts.  These modalities promote interactive, learner-centered feedback processes across varied learning environments. The analysis highlights four key educational outcomes: improvements in writing proficiency, enhanced feedback literacy, increased learner engagement and reflection, and the development of learner autonomy and self-regulation. These outcomes demonstrate a consistent pedagogical value of dialogic feedback in supporting active learning ecosystems. Research trends reveal three chronological phases: early conceptual exploration, empirical classroom application, and recent growth in digital feedback practices. Studies predominantly employ sociocultural theory, dialogic pedagogy, feedback literacy, and self-regulated learning frameworks. Methodologically, the field has advanced from qualitative designs to mixed method and quasi-experimental approaches, mostly within Asian EFL university writing contexts. Notable gaps include the lack of longitudinal studies, minimal focus on speaking skills, and underrepresentation of diverse geographical and educational contexts. Future research should address these gaps by expanding skill focus, geographical coverage, and methodological rigor to ensure more equitable and effective dialogic feedback practices in ELT.